2018
DOI: 10.1002/jez.b.22792
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and transcriptomic analyses reveal three discrete primary stages of postembryonic development in the common fire salamander, Salamandra salamandra

Abstract: The postembryonic development of amphibians has been characterized as divided into three predominant periods, hereafter named primary developmental stages: premetamorphosis (PreM), prometamorphosis (ProM), metamorphic climax (Meta), and completion of metamorphosis (PostM), largely based on examination of anuran development. Here, we categorized the postembryonic development of larvae of a poisonous fire salamander (Salamandra salamandra) by integrating morphology and gene expression (transcriptomic) data. Morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 108 publications
(185 reference statements)
0
24
0
Order By: Relevance
“…To date, the metabolic pathways that allow some amphibians to synthesize or sequester alkaloids are poorly studied. In the specific case of the fire salamander (see Lüddecke et al, ), we know that their steroidal alkaloids are self‐synthesized using cholesterol as one of the precursor molecules (Habermehl & Haaf, ), and that their synthesis begins at prometamorphosis (Sanchez, Küpfer et al,). This has led to the idea that thyroid hormones might play a role in salamander alkaloid synthesis, as thyroid hormones are known to regulate the metabolism of cholesterol (Tata, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the metabolic pathways that allow some amphibians to synthesize or sequester alkaloids are poorly studied. In the specific case of the fire salamander (see Lüddecke et al, ), we know that their steroidal alkaloids are self‐synthesized using cholesterol as one of the precursor molecules (Habermehl & Haaf, ), and that their synthesis begins at prometamorphosis (Sanchez, Küpfer et al,). This has led to the idea that thyroid hormones might play a role in salamander alkaloid synthesis, as thyroid hormones are known to regulate the metabolism of cholesterol (Tata, ).…”
Section: Discussionmentioning
confidence: 99%
“…Each extract was evaporated to 100 μl in total, and 1 μL of this concentrated extract was used for gas chromatography. The peaks of samandarine, samandarone, and O-acetylsamandarine were identified based on their retention times, as reported in Sanchez, Küpfer et al (2018). Because samandarine and samandarone had very similar retention times, their peaks overlapped in the chromatograms and we, therefore, did not further differentiate between them.…”
Section: Alkaloid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…() found no quantitative correlation between an individual's conspicuousness (chromatic and achromatic contrasts) and the alkaloid content in post‐metamorphic fire salamanders. A recent developmental study, however, showed that the synthesis of alkaloids starts with the establishment of the typical conspicuous coloration during metamorphosis (stage ProM), thus indicating an unambiguous qualitative correlation between colour and alkaloid production (Sanchez et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the main component is represented by steroidal alkaloids of the samandarine type (hereafter referred to as SAMs). Nine members of this class of alkaloids were previously described; the three SAMs samandarine, samandarone and O-acetylsamandarine are considered to be the main alkaloids in salamander skin poison (Vences et al, 2014;Sanchez et al, 2018b). Although SAMs might provide an antimicrobial defence (Habermehl & Preusser, 1969, 1970Preusser et al, 1975), they are mostly known for their physiology-disrupting capacities in vertebrates; acting as convulsive neurotoxins that can cause lethal intoxication even in large mammals such as dogs (Erjavec, Lukanc & Zel, 2017).…”
Section: Introductionmentioning
confidence: 99%